THE EFFECT OF DIGITAL MARKETING AND PRODUCT QUALITY ON INCOME INCREASE AT PAPUA GALLERY - Andrei Maryen; Meyta Longkutoy; Yulita Komboy (RADJA PUBLIKA, 2025)
The purpose of this study was to determine the effect of digital marketing and product quality variables on revenue at the Papua Gallery. The analysis technique used in this study was quantitative descriptive, using multiple linear regression. The results of this study are: Hypothesis 1 can be said to have an effect of digital marketing on Papua Gallery's revenue, because the significance value is less than 5% (0.0317 < 0.05), and the calculated t-value is greater than the t-table (2.215 > 2.052), thus H2 is accepted. Hypothesis 2 can be said to have an effect of product quality on Papua Gallery's revenue, because the significance value is less than 5% (0.007 < 0.05), and the calculated t-value is greater than the t-table (3.156 > 2.052), thus H1 is accepted. The F-test was used to examine the effect of the independent variables, namely digital marketing and product quality, together on the y variable (revenue). The F test uses the ANOVA table or F test, so that variables X1 and X2 together have an effect on Y.